(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aimed to analyze the contents of the Arabic language textbook ’My Language for the basic fourth class to identify to which extent it included oral communication skills (listening skill, talking skill). The researcher adopted the content analysis method of the descriptive methodology, as for the research sample, it was the Arabic language textbook ’my language of the first semester , which contains only three units, and is prescribed for the fourth class by the Syrian Ministry of Education for the school year 2020/2021, and the research tool was an analysis form for oral communication skills, based on a list prepared by the researcher, it included (56) oral communication skills distributed into (30) talking skills and (26) listening skills. The researcher reached the following conclusions: The listening skills were emphasized in ’My language textbook for the basic fourth Class and got the number of repetitions of (72) with a percentage of (64.86%). As for talking skills, they came with (39) repetitions and a percentage of (35.14%). The results also showed that the oral communication skills that were most emphasized are two skills (focusing attention on the main idea, focusing attention on the sub-idea). Based on these results, the researcher made several proposals, the most important of which are: Paying attention to the need to include oral communication skills in which there was a clear weakness in the content of the Arabic language textbook ’My Language of the basic fourth class, and to support the content with intended activities that help to provide basic fourth class students with oral communication skills.